#### Answer

$=\frac{2c-9}{2c+8}$

#### Work Step by Step

$\frac{4c^2-36c+81}{4c^2-2c-72}$
$=\frac{(2c-9)(2c-9)}{(2c+8)(2c-9)}$
$=\frac{2c-9}{2c+8}$

Chegg costs money, GradeSaver solutions are free!

Published by
Prentice Hall

ISBN 10:
0133281140

ISBN 13:
978-0-13328-114-9

$=\frac{2c-9}{2c+8}$

$\frac{4c^2-36c+81}{4c^2-2c-72}$
$=\frac{(2c-9)(2c-9)}{(2c+8)(2c-9)}$
$=\frac{2c-9}{2c+8}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.